Heat Waves and occupational injuries: the importance of a consistent working definition. (13th November 2019) - Riccò, M; Balzarini, F; Mezzoiuso, A G
Abstract: Introduction: Heatwaves (HWs) have been linked with increased risk of occupational injuries (OIs). As no consistent definition of HW is globally acknowledged, also the actual impact of HWs on the workplaces is not well defined. Background and aims: Daily numbers of workers compensation claims from all Northern Italy (2013 to 2017, warm season: April to September) from Agricultural and Industry economic sectors (n = 1, 907, 122) were associated with daily weather data. The impact of average (Tday) and maximum (Tmax) daily temperatures on the risk of OIs was assessed using a time-stratified case-crossover study. HW was defined by 3 or more days having Tday > 97.5th percentile or by Tmax exceeding 5 °C or more historical reference. Results: A total of 1161205 OIs were retrieved (94.4% from industrial sector). Assuming Tday < 90th percentile as the referent category, the risk for OIs was higher for Tday exposure 95 to 97.5th percentiles (OR 1.43, 95%CI 1.09-1.20 for agriculture; OR 1.40, 95%CI 1.03-1.05 for industry) and for exposures exceeding 97.5th percentiles (OR 1.14, 95% CI 1.09-1.20, OR 1.02, 95%CI 1.01-1.03, respectively), and for days characterized by Tmax > 35 °C (OR 1.27, 95%CI 1.21-1.33; 1.03 95%CI 1.02-1.04). An increased risk for OIs was similarly identified during HWs defined by Tday (OR 1.15, 95%CI 1.08-1.23 for agriculture; OR 1.06, 95%CI 1.05-1.08 for industry), while HWs defined by Tmax were characterized by increased risk only for agricultural workers (OR 1.14, 95%CI 1.12-1.16). Discussion: Days characterized by very high temperatures were associated with the greatest risk of OIs in the industrial and agricultural settings. As a working definition for HW based on maximum temperatures apparently missed a possible increased risk for OIs in the industrial sector identified by average daily temperatures, our results stress the urgent need for a common and shared definition of HWs, allowing potential stakeholder to put in place appropriate prevention strategies. Key messages: High environmental temperatures are associated with an increased risk of occupational injuries. Different working definitions of Heat Wave may lead to missing the actual risk for occupational injuries. A shared definition is therefore strongly needed.